“The Role of Drawing in Developing Visual Literacy and Artistic Skills in Students” - Rustamov Axtam Muxtorovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines the role of drawing in enhancing students’ visual literacy and artistic skills in visual arts education. It highlights how drawing exercises contribute to the development of creative thinking, aesthetic sensitivity, and technical competence. The article also discusses methods to integrate traditional motifs and cultural elements into drawing activities to foster cultural awareness and a deeper appreciation for national heritage.